Using a Novel Heterojunction CoWO4/g-C3N4 as Visible Light Photocatalyst for Photodegradation of Organic Pollutant - Van Dang, Do; Linh, Tran Thi Chi; Son, Le Thanh (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 3, 2023)
Methylene Blue (MB) is a common dye that has various applications in different fields, including medicine, biology, and environmental science. While it can be beneficial in certain contexts, it can also have negative effects on the environment under certain circumstances. In this study, the photodegradation of MB under visible light irradiation using a novel heterojunction CoWO 4 /g-C 3 N 4 catalyst was investigated. A series of CoWO 4 /g-C 3 N 4 composites were synthesized and characterized using various techniques, including XRD, SEM, SEM-EDS, FT-IR, and UV–DRS. The results revealed that the 0.3CoWO 4 /g-C 3 N 4 composite showed the highest efficiency (93%) in degrading MB during the 80-minute photodegradation process, aligning with the pseudo-first-order kinetics. The results provide clear evidence that the formation of CoWO 4 /g-C 3 N 4 heterojunction greatly enhances the efficiency of photocatalysis by facilitating the swift separation of electron-hole pairs and boosting the redox capability. Additionally, the photodegradation efficiency remained above 90% even after four cycles, suggesting the stability of the catalyst.